2014
DOI: 10.1007/s00432-014-1756-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in TS, MTHFR and ERCC1 genes as predictive markers in first-line platinum and pemetrexed therapy in NSCLC patients

Abstract: Purpose We presented retrospective analysis of up to five polymorphisms in TS, MTHFR and ERCC1 genes as molecular predictive markers for homogeneous Caucasian, non-squamous NSCLC patients treated with pemetrexed and platinum front-line chemotherapy.MethodsThe following polymorphisms in DNA isolated from 115 patients were analyzed: various number of 28-bp tandem repeats in 5′-UTR region of TS gene, single nucleotide polymorphism (SNP) within the second tandem repeat of TS gene (G>C); 6-bp deletion in 3′-UTR reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…(2014)Asian (China)235180/5558 (29–84)IIIA-IVDDP+TAX/DOC/GEMOR, OSPCR-CTTP XRCC1 rs25487 103 Zhou, M. (2014)Asian (China)9356/3761.5 (NR)IIIB-IVDDP+GEMORPCR-RFLP XPD rs13181 rs1799793, CDA rs2072671 104 Zhao, X. (2014)Asian (China)192132/6060.8 (26–79)IIIA-IVPlatinum-basedOR, OSMALDI-TOF-MS ERCC1 rs3212986 rs11615 rs2298881 105 Lv, H. (2014)Asian (China)9154/3759 (34–80)IIIB-IVDDP+TAX/GEM/NVPORTaqMan-MGB GSTP1 rs1695 106 Krawczyk, P. (2014)Caucasian (Poland)11559/5661 (NR)II-IVDDP/CBP+PEMOSHRM, PCR-RFLP ERCC1 rs11615 107 Sullivan, I. (2014)Caucasian (Spain)161125/3663.7 (36–85)IIIA-IVDDP/CBP-basedOR, OSDynamic array chips ERCC1 rs3212986 rs11615, XPD rs13181 rs1799793, XPG rs1047768 rs17655, XRCC1 rs25487 rs1799782, rs25489, XPA rs1800975 108 Dong, C M. (2014)Asian (China)9238/5457 (40–6)IIIB-IVPlatinum-basedORPCR-RFLP MTHFR rs1801133 109 Liu, D. (2014)Asian (China)378297/8162.4 (36–78)I-IVDDP+GEM/DOC/NVP/TAXOR, OSPCR-RFLP XPG rs1047768 rs17655 XRCC1 rs25487 rs1799782 110 Kou, G. (2014)Asian (China)5014/3656 (45–78)IIIB-IVDDP+NVPORPCR-RFLP ERCC1 rs3212986 111 Kalikaki, A.…”
Section: Resultsmentioning
confidence: 99%
“…(2014)Asian (China)235180/5558 (29–84)IIIA-IVDDP+TAX/DOC/GEMOR, OSPCR-CTTP XRCC1 rs25487 103 Zhou, M. (2014)Asian (China)9356/3761.5 (NR)IIIB-IVDDP+GEMORPCR-RFLP XPD rs13181 rs1799793, CDA rs2072671 104 Zhao, X. (2014)Asian (China)192132/6060.8 (26–79)IIIA-IVPlatinum-basedOR, OSMALDI-TOF-MS ERCC1 rs3212986 rs11615 rs2298881 105 Lv, H. (2014)Asian (China)9154/3759 (34–80)IIIB-IVDDP+TAX/GEM/NVPORTaqMan-MGB GSTP1 rs1695 106 Krawczyk, P. (2014)Caucasian (Poland)11559/5661 (NR)II-IVDDP/CBP+PEMOSHRM, PCR-RFLP ERCC1 rs11615 107 Sullivan, I. (2014)Caucasian (Spain)161125/3663.7 (36–85)IIIA-IVDDP/CBP-basedOR, OSDynamic array chips ERCC1 rs3212986 rs11615, XPD rs13181 rs1799793, XPG rs1047768 rs17655, XRCC1 rs25487 rs1799782, rs25489, XPA rs1800975 108 Dong, C M. (2014)Asian (China)9238/5457 (40–6)IIIB-IVPlatinum-basedORPCR-RFLP MTHFR rs1801133 109 Liu, D. (2014)Asian (China)378297/8162.4 (36–78)I-IVDDP+GEM/DOC/NVP/TAXOR, OSPCR-RFLP XPG rs1047768 rs17655 XRCC1 rs25487 rs1799782 110 Kou, G. (2014)Asian (China)5014/3656 (45–78)IIIB-IVDDP+NVPORPCR-RFLP ERCC1 rs3212986 111 Kalikaki, A.…”
Section: Resultsmentioning
confidence: 99%
“…This among other polymorphisms has been suggested as molecular predictive markers by some publications in both SCLC and NSCLC [32,33]; but the results are not encouraging enough to promote these tests in the regular practice.…”
Section: Pemetrexedmentioning
confidence: 89%
“…While several studies have shown that an increased number of 28-bp variable number tandem repeat (VNTR) sequences in the 5′-UTR of the TYMS gene (i.e. the 3R/3R genotype) and/or a 6-bp insertion/deletion polymorphism in the 3′-UTR of TYMS may influence outcomes with pemetrexed, 10,11,13,15 others have demonstrated opposite results or no association at all. 12-14 Similarly, two prior studies concluded that NSCLC patients who were homozygous for a substitution of thymine for cytosine in nucleotide 677 of the MTHFR gene (i.e.…”
Section: Discussionmentioning
confidence: 99%